Faktor-faktor yang Berhubungan dengan Learning Agility: A Systematic Literature Review - Gresika Tabitha Vinesian; Suryanto Suryanto; Reza Lidia Sari (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
The current situation in the world is experiencing VUCA, where there are rapid and drastic changes in technology, economics, the environment, and other aspects. Every adult, especially employees and job seekers, needs to develop learning agility so that they can adapt and compete in today's era. This systematic literature review aims to identify the factors related to learning agility. Article searches were conducted from March to June 2022 using six databases, namely SpringerLink, Emerald Insight, ScienceDirect, SAGE, Scopus, and ProQuest, with keywords